Measuring the benefit of Islamic unit linked for customer by ANP (Analytic Network Process) - Siregar, Saparuddin; Kholis, Nur; Nasution, M. Yasir (Universitas Islam Indonesia, 2018)
This research aims to analyze the customer benefit of Islamic unit link by ANP method (Analytic Network Process). The analysis resulted that the value of inconsistency index < 0,1, it means that all respondents are consistent in answering the questionnaire. W value of opportunity and benefit cluster is 1; it means all respondents have complete agreement. While W value of cost cluster is 0,18 and risk cluster is 0,15. It means that agreement among respondents is lower. The most dominance cost is acquisition cost (2.49273), and the most dominance risk is discomply to Syariah risk (2.71049). The score of benefit cluster for the customer is lower than Cost cluster (6.52) and Risk cluster (6.83), because of benefit cluster score 6.21. In answering choice between buying or don't buy Syariah unit link, attention must be paid to opportunity cluster score, namely 4.75. It is lower than benefit, cost, and risk cluster. It shows that Syariah unit link is offering a lower opportunity to gain financial benefit than bearing cost and risk.